The Exploration of Projects’ Failure Factors in Oil & Gas Industry in UAE - Al Hashmi, Saleh Ahmed Saleh (2013)
As everybody usually says that project is the mean for changes and developments, so it is very important to know how this mean can be effectively used and safely protected. Normally, the concept of project is applied through the implication of project management knowledge, process, and procedure which is generally identified by some international organizations such as Project Management Institute. Knowing how to apply this knowledge is not that difficult, but the success on how to protect the application of this knowledge from the surrounded effects, which could lead any project to fail, is the real puzzle. Therefore, in this work I will try to explore the reasons behind project failure in oil and gas industry especially in one of UAE Gas Production Company. These reasons were developed and they were ranked using technique of Critical Failure Factors (CFF) analysis. In order to evaluate the reasons for project failure through the determined CFFs, a comprehensive literature review was performed. CFFs relevant to the domain of the study were grouped under three main areas, which were procurement, scope of work, and communication management. These CFFs and their groups were tested empirically through two successive surveys. In the first survey, each of the CFF’s group was tested based on a five points lickert scale (1 being extremely disagree, 5 being extremely agree and 3 being neutral). This survey aimed to confirm the importance and relatedness of these subjects to GPC overhaul projects. Based on this confirmation the CFFs were gathered under these groups. Then, second survey was carried out. In the second survey CFFs were individually ranked under each group using same method as in the first survey but with different linkrt scale criteria (1 being least important, 5 being important and 3 being neutral). As result of the methodology that used and the evaluation that followed, a list for the most five critical CFFs under the three above mentioned groups was developed. In addition, some recommendations were proposed as protective actions or solutions to ensure the success for the future overhaul projects in the targeted company. In conclusion, the determined model of CFF grouping and gradation of each CFF can be effectively used as a tool to deploy better project management process for overhaul projects with the intention to reduce the probability of failure for such projects.